2007
DOI: 10.1177/0748233707076810
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-specific health consultation for chromated copper arsenate chemical mixture: port of Djibouti

Abstract: The Agency for Toxic Substances and Disease Registry (ATSDR) prepared this health consultation to provide support for assessing the public health implications of hazardous chemical exposure, primarily through drinking water, related to releases of chromated copper arsenate (CCA) in the port of Djibouti. CCA from a shipment, apparently intended for treating electric poles, is leaking into the soil in the port area. CCA is a pesticide used to protect wood against decay-causing organisms. This mixture commonly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 112 publications
1
9
0
Order By: Relevance
“…18 The few studies done amongst CCA-exposed workers in a wood-preserving plant reported no adverse health effects amongst workers, but the number of participants was small. 2 As mentioned before, As and Cr are associated with a number of cancer-related and non-cancer-related health effects (Table 4). Health effects resulting from combined exposure to As and Cr may be additive, but there is no evidence of any interaction between these metals.…”
Section: Health Implications Of Urinary Cr Cu and As Levelsmentioning
confidence: 79%
See 2 more Smart Citations
“…18 The few studies done amongst CCA-exposed workers in a wood-preserving plant reported no adverse health effects amongst workers, but the number of participants was small. 2 As mentioned before, As and Cr are associated with a number of cancer-related and non-cancer-related health effects (Table 4). Health effects resulting from combined exposure to As and Cr may be additive, but there is no evidence of any interaction between these metals.…”
Section: Health Implications Of Urinary Cr Cu and As Levelsmentioning
confidence: 79%
“…Health effects resulting from combined exposure to As and Cr may be additive, but there is no evidence of any interaction between these metals. 2 Interestingly, there was a high prevalence of respiratory, diarrhoeal and skin problems reported amongst participants, which requires more detailed epidemiological investigation; these symptoms might be a result of other environmental exposures in the communities and the self-reports are too crude a measure of these health problems. The self-reports were included in this study merely to provide preliminary evidence of health effects as the aim of the study was to determine the level of exposure of the participants to CCA.…”
Section: Health Implications Of Urinary Cr Cu and As Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, concerns have been raised owing to the high levels of arsenic and chromium concentrations in CCA treated wood, due to the potential human contact in occupational environments and to the ecological exposure (Chou et al, 2007;Zartarian et al, 2006). In this perspective, concerns about the safety of children have prompted more attention.…”
Section: Human Exposure To Chromated Copper Arsenatementioning
confidence: 99%
“…Besides CCA, ammonium copper quaternary (ACQ) and copper boron azole (CBA) are available on the market [11]. Prior to the 1940s, lead compounds were commonly used as colouring agents in paints [12].…”
Section: Introductionmentioning
confidence: 99%